ED SCHOOL FOLLIES: THE MISEDUCATION OF AMERICA'S TEACHERS (Author: Rita Kramer) - Mandzuk, David; Clifton, rodney (Revue des sciences de l'éducation de McGill, 1994)
Rita Kramer. ED SCHOOL FOLLIES: THE MISEDUCATION OF AMERICA'S TEACHERS. New York: The Free Press, 1991. 222 pp. $22.95 US.